The Role of Business Incubators in Facilitating the Growth of Creative Startup Companies - Lee, Ava; Tan, Jaden; Chan, Rachel (Journal of Social Entrepreneurship and Creative Technology, 2024)
The rise of creative startups has become an important phenomenon in today’s entrepreneurial landscape. These companies, often operating in industries such as design, media, technology, and entertainment, play a crucial role in driving innovation and economic growth. Business incubators have emerged as key players in supporting the development and growth of these startups by providing essential resources, mentoring, and networking opportunities. However, the specific role and impact of business incubators on creative startups remain underexplored, particularly in the context of their long-term growth and sustainability. This study aims to examine the role of business incubators in facilitating the growth of creative startup companies. It seeks to understand how incubators contribute to the development of creative industries by providing both tangible and intangible support to entrepreneurs. The research adopts a mixed-methods approach, utilizing both qualitative interviews with incubator managers and creative entrepreneurs and quantitative surveys to assess the impact of incubator support on startup performance. Data was collected from several business incubators in key startup hubs. The findings indicate that business incubators play a critical role in providing creative startups with access to funding, mentorship, networking opportunities, and workspace. Startups that participated in incubator programs showed significantly higher rates of growth, innovation, and market readiness compared to those outside the incubators. Business incubators are essential for the success and growth of creative startups. Their support mechanisms help bridge the gap between idea development and market execution, contributing to the overall success and sustainability of creative industries.